Analisis Perbandingan Nilai Kondisi Jalan Menggunakan Metode SDI dan IRI Dari Alat Survei Roadroid: Comparative Analysis of Road Condition Values Using the SDI and IRI Methods from the Roadroid Survey Tool - Utama, Novan Rezki; Arliansyah, Joni; Kadarsah, Edi (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2023)
Good road infrastructure plays an important role in the economic development of a city. Therefore, the government must maintain and improve road conditions yearly to help attract investment and ultimately lead to overall economic growth. Presently, road condition surveys are conducted and assessed using the manual method with the Surface Distress Index (SDI), which is time-consuming and expensive due to the large number of access roads. In order to address this issue, a fast and cost-effective alternative survey approach is required, such as the International Roughness Index (IRI) method using the Roadroid application. Roadroid is an application installed on a smartphone and then attached to a car's windshield to record road conditions while the car is in motion. This study aims to compare the use of the Roadroid application with the manual survey method in terms of time and cost efficiency in identifying road conditions in the city of Palembang, which has 1204 roads. In this study, the Roadroid application results is compared to the road condition assessment results from the SDI methods. The results showed that the time required to obtain road conditions with manual survey and Roadroid application was 37.313 minutes and 4.123 minutes, respectively. The cost required to obtain road conditions was IDR 290.937.000 and IDR 68.006.000 for manual surveys and using the Roadroid application, respectively. Furthermore, the comparison of road condition assessment results between the SDI and IRI methods showed that they have average mean differences of 24.86%, so it can be concluded that the road conditions obtained in the IRI method using Roadroid have high accuracy with the conditions in the SDI method. From the results, it can be concluded that using the Roadroid application to obtain road conditions is more effective and efficient than manual surveys.